“Son mías las fronteras que crucé”: dores e resiliência no deslocamento forçado de venezuelanas ao Brasil - Muniz, Flávia de Moura Rocha Parente (2020)
Faced with the social, political and economic crisis in Venezuela, Venezuelan women and men cross the border with Brazil, located in Roraima, in search of decent living conditions. Given that social constructions make it easier for people to experience forced migration in different ways depending on gender, this study aimed to investigate the process of forced displacement of Venezuelan women to Brazil, especially with regard to the psychological and social impacts of this experience. we studied the cases of three migrant women, Venezuelans, living in shelters for refugees in Roraima, between 29 and 45 years old, with the length of stay in Brazil between 8 and 18 months. The conceptual support on which this Thesis is based is in the intertwining of each base of a theoretical tripod: Hobfoll's Conservation of Resources Theory (COR), the gender perspective and Anzaldúa's poetic-theoretical apparatus as a possibility of understanding the “borderland”. The results reveal that the loss of resources occurs in the pre-migratory and postmigratory context, relating and showing spiral of losses, and are closely related to the social construction of gender. Such losses and the way each person deal with them are related to the life story and possibilities of building and maintaining resources. Previous coping resources and engagement proved to be possible strategies in the face of situations of loss spiral and traumatic stress. To facilitate the development of resilience and favor the engagement process, it showed to be relevant that the humanitarian response invests in possibilities of (re)building resources, in strengthening social support and that women are participants in the intervention development processes. For the strengthening of a Latin American Humanitarian Psychology, it is important and urgent to simultaneously learn from the Humanitarian Psychology built in the global north and recognize the specificities of the region in order to offer a culturally sensitive, effective and sustainable psychosocial support to people in need of international protection